How the Danes Discovered Britain: The International Integration of the Danish Dairy Industry Before 1880 - Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2014)
The success of Danish agricultural exports at the end of the nineteenth century is often attributed to the establishment of a direct trade with Britain. Previously, exports went mostly via Hamburg, but this changed with the loss of Schleswig and Holstein to Prussia in the war of 1864. After this, quantity and price data imply narrowing price gaps and thus imply gains for Danish producers. Why then did Denmark not discover the British market earlier? We show that butter markets in both countries were integrated in the eighteenth century, but through the Hamburg hub. We then demonstrate that there were sound economic reasons for this well into the nineteenth century. However, movements to establish a direct trade were afoot from the 1850s. Thus, although the war certainly gave an extra boost to the process, the shock from the loss of the Duchies was not necessary for the future Danish success.
Keywords: F1; L1; N5; N7; Q1; 330; Butter; dairies; Denmark; hubs; international trade; market integration